Modelling and measuring business risk and the resiliency of retail banks - Mohamed Chaffai; Michel Dietsch (Deutsche Bundesbank, 2013)
The recent banking crisis has revealed the existence of strong resiliency factors in the retail banking business model. On average, retail banks suffered less than other financial institutions from unexpected market changes. This paper proposes a new methodology to measure retail banks' business risk, which is defined as the risk of adverse and unexpected changes in banks' profits coming from sudden changes in the banks' activities. This methodology is based on the efficiency frontier methodology, and, more specifically, on the duality property between the directional distance function and the profitfunction. Using the distance function to compute banks' profitability, we take the distance to the frontier of best practices as a measure of profit inefficiency, ie of unexpected losses related to underperformance. In this approach, shifts in the efficiency frontier induced by adverse shocks to banks' volumes serve as a measure of business risk. This measure of profit volatility allows a measurement to be made of the impact of volume changes on banks' profits. This method is applied to a database containing halfyearly regulatory accounting reports over the 1993-2011 period for more than 90 French banks running a retail banking business model. Our results verify a low level of business risk in retail banking, thus confirming the resiliency of the retail banks' business model.
Keywords: G21; D24; 330; Bank solvency; Retail Banking; Business Risk; Efficiency Analysis; Profit Frontier